Assessing seafloor morphological changes of offshore islands based on bathymetry using Sentinel-2 images: a case study in the Truong Sa Islands (Vietnam) - Nguyen, Nhu Hung; Trinh, Le Hung; Le, Van Phu; Nguyen, Van Son (Bulletin of Geography. Physical Geography Series, 2025)
Assessing seafloor morphological changes plays a crucial role in understanding environmental processes, helping to predict changes in marine ecosystems, protect natural resources, and support sustainable management of marine areas. This study proposes an effective and accurate method for assessing seafloor morphological changes using Sentinel-2 satellite data. The research focuses on analyzing depth and topographic features of offshore islands, with the study area extending 9 km in length and 1.8 km in width, including a semi-enclosed lagoon with depths ranging from 3 to 6 meters. The images were collected at three time points: January 14, 2020; June 5, 2020; and June 15, 2021. Surface reflectance images from the blue and green bands were used to estimate bathymetry. Additionally, the study utilized the Random Forest algorithm on the GEE platform to classify the objects of interest. The results show an increase in the average depth of submarine sand from 2.07 m to 2.17 m, while coral showed a change from 0.96 m to 2.20 m. Coral sand floor and substrate grass also exhibited significant changes in depth, with coral sand floor decreasing from 9.45 m to 6.08 m and substrate grass decreasing from 8.04 m to 6.15 m. Objects such as solid bottom and seagrass maintained stable depths with minor variations. Moreover, field data and tide measurements were used to validate and adjust the bathymetric models, enhancing the accuracy of the estimates.